Hamstring-and-lower-back flexibility is not related to hamstring-and-lower-back injuries in elite female soccer players - Versteeg, J. P. M.; Thijs, K. M.; Zuithoff, N. P. A.; Backx, F. J. G.; Huisstede, B. M. A. (Translational Sports Medicine, 2021)
Objectives: Although muscle flexibility is considered to be a risk factor for hamstring-and-lower back injuries (HLB-injuries) in male soccer players, it is unclear whether this is true for elite female soccer players. Design: Prospective observational cohort study. Method: One hundred fourteen elite female soccer players were monitored during the 2014-2015 soccer season. Hamstring-and-lower-back flexibility (HLB-flexibility) was assessed using the sit-and-reach test (SRT) and soccer exposure and soccer-related injuries were registered. Poisson regression was used to study the association between HLB-flexibility and HLB-injuries with adjustment for possible confounders. Results: Of the 114 players, 46 (40%) reported an HLB-injury (60 hamstring injuries and 20 lower back injuries) during the season, accounting for 22% of all injuries reported. No significant association was found between HLB-flexibility and HLB-injuries (P = .534). Also, after correction for potential confounders (age, weight, height, match exposure, and training exposure), HLB-flexibility was not found to be associated with HLB-injuries ((1.027 (0.989-1.066) (RR 95% CI)), P = .164 unadjusted, and 1.022 (0.987-1.059), P = .217 adjusted). Match exposure was significantly associated with HLB-injuries. When the number of match hours increased by 1, the number of HLB-injuries increased by a factor 1.051. Conclusion; HLB-flexibility does not influence the occurrence of HLB-injuries in elite female soccer players.